Dorothea Lange with Paul Schuster Taylor - Rondal Partridge:::Creator::::::::::::
Dorothea Lange interacts with Paul Schuster Taylor, her second husband and noted agricultural economist from UC, Berkeley, 1896-1984. Lange's photographs influenced the development of documentary photography and humanized the consequences of the Great Depression.